Screen time and its determinants in infants and toddlers: results from a metropolitan area of İstanbul - Kurap Öcebe, Didem; Güney, Rabiye (Journal of Dependence, 2025)
Objective: This cross sectional study aimed to assess screen time and associated factors in infants and toddlers under the age of 3 years in a metropolitan area.Method: Data were collected from 269 mothers registered in a family health center using a questionnaire. The questionnaire examines the demographic characteristics of families, the time spent by infants and toddlers with screen devices, and factors that may affect screen time, such as income status, education level and resources.Results: Three-quarters of infants and toddlers in this sample used screen devices (n=202, 75.1%). Total screen time ranged from 20 to 270 min/day, with a mean of 101.8±56.2 min/day. Infants and toddlers spent an average of 71.9 min/day watching television, 63.1 min/day using tablets, and 36.85 min/day using mobile phones. Total daily screen time exceeded World Health Organization (WHO) recommendations in 36.3% of infants aged 0-12 months, 84.3% of toddlers aged 13-24 months, and 49.4% of toddlers aged 25-36 months. Age of infant and toddler, maternal education level, and family income were identified as factors associated with risky screen exposure.Conclusion: Families can be educated about the potential consequences of screen time and strategies to reduce screen use. In trainings, families in the risk group should be given priority in terms of factors affecting screen time such as income status, education level and age.
Keywords: Infant; toddler; screen time; technology addiction